An acoustic investigation of English vowels as produced by English L1 and Setswana L1 foundation phase learners - Prinsloo, Danie J. (Daniel Jacobus), 1953- (University of Pretoria, 2017)
Thesis (DPhil)--University of Pretoria, 2016.